PENGARUH UKURAN PERUSAHAAN,MANAJEMEN LABA,TARIP PAJAK EFEKTIP,PERATA LABA,KONSERVATISMA TERHADAP BEDA LABA AKUNTANSI DENGAN LABA PAJAK - Hotman T. Pohan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
The objective of this research is to prove the factors that assumed influence book -tax different significantly or not. The method of this research is multivariate analysis with independent variables are size, earning management, effective tax rate,income smoothing and conservatism.The result of this research, is that earning management influence negatively and significantly toward book- tax difference, income smoothing influence positively and significantly,conservatism influence positive and significantly toward boo-tax difference, mieanwhile size and effective tax rate has no influence toward book-tax difference, simultaniosly all factors significantly influence toward book-tax different with coefficient determination 26,5%..Keyword : book-tax different, size,earning management, effective tax rate, income smoothing, conservatism.